Ultra-high phosphorus-doped epitaxial Ge layers grown by HWCVD method on Si substrates. (September 2019) - Shengurov, Vladimir; Denisov, Sergei; Chalkov, Vadim; Trushin, Vladimir; Zaitsev, Andrei; Prokhorov, Dmitry; Filatov, Dmitry; Zdoroveishchev, Anton; Ved, Mikhail; Kudrin, Alexey; Dorokhin, Mikhail; Buzynin, Yuri
Abstract: The conditions for obtaining high-quality heavily doped epitaxial Ge:P/Si(001) epitaxial layers by hot wire chemical vapor deposition were determined. The thermal decomposition of GaP was employed to provide the source of P. Extremely high electron concentration in Ge layers (up to 1.3×10 20  cm −3 ) were achieved. According to the secondary ion mass spectroscopy data, the P concentration was constant within the entire thickness of the Ge layers and drops down abruptly at the boundary with the Si buffer. A strong direct bandgap edge photoluminescence line has been observed from the heavily doped n + -Ge:P layers at room temperature.